PHYSICAL AVAILABILITY OF DRUGS USED FOR TREATMENT OF ASTHMA IN CHILDREN - I.A. Kostiuk (Bogomolets National Medical University, 2017)
The article presents the results of the study of the physical availability of drugs used for the treatment of asthma in children, among 186 municipal and private pharmacies in Kyiv. According to the results, we found low physical availability of the study group. The trade names of drug with the highest physical availability were allocated.